Research on Spatial Pattern and Accessibility of Traditional Villages-Taking Henan Province as an Example - H. Tian; X. Liu; R. Wang (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2024)
Chinese culture has a long history. Traditional villages carry the breath of history. The great cultural attraction of traditional villages to people and the implementation of rural revitalization policies, it makes the attention to traditional villages gathered. Henan Province has a deep cultural heritage, he has many traditional villages, widely distributed. Therefore, it is particularly important to study the spatial pattern and accessibility of national-level traditional villages in Henan Province. This study takes 275 national-level traditional villages in Henan Province as research objects, using GIS analysis with accessibility to study the spatial pattern of traditional villages in Henan Province and to demonstrate the accessibility of traditional villages in prefectural-level cities in Henan Province at the municipal scale. Studies have shown that the spatial pattern and accessibility of the distribution of traditional villages in Henan Province are closely related to many factors (transportation road network, distance from the central city, etc.). The accessibility values of traditional villages in each prefecture-level city vary greatly, indicating that there are obvious differences in the accessibility of traditional villages in Henan Province. It intuitively reflects the spatial distribution and accessibility of traditional villages in Henan Province, with a view to providing a reference for the tourism development of traditional villages. Providing an analytical basis for promoting the optimal allocation of traditional village resources.